HOW GREEN MARKETING MIX INFLUENCES CONSUMER BEHAVIOUR TOWARD ORGANIC AGRICULTURAL PRODUCTS: EVIDENCE ON THE MEDIATING ROLES OF TRUST AND PERCEIVED VALUE - Suchira Promsri and Sarapee Chanatup Chutimant Boonnual (Zenodo (CERN European Organization for Nuclear Research), 2026)
This study examines how green marketing mix influences consumer behaviour toward organic agricultural products, with particular attention to the mediating roles of trust and perceived value. Using a quantitative research design, data were collected from 400 consumers of organic agricultural products and analyzed using partial least squares structural equation modelling (PLS-SEM). The results indicate that green marketing mix has a robust positive effect on trust and a significant direct effect on consumer behaviour. Trust, in turn, shows a stable positive association with consumer behaviour. By contrast, the value-related direct paths are weaker and should be interpreted with caution. Although green marketing mix is positively associated with perceived value, and perceived value is positively related to consumer behaviour, these direct effects are statistically fragile when evaluated against confidence-interval criteria. Despite this qualification, the mediation analysis reveals that both trust and perceived value transmit the effect of green marketing mix on consumer behaviour, with the indirect pathway through perceived value showing a comparatively stronger magnitude. The findings therefore suggest that green marketing mix shapes consumer behaviour not only through direct market influence, but also through internal evaluative mechanisms, especially consumers’ trust formation and value assessment. The study contributes to the green marketing and sustainable consumption literature by moving beyond purchase intention and offering a broader, mechanism-based explanation of consumer behaviour in the organic agriculture context. Practically, the results imply that marketers should prioritize credibility-building strategies, transparent communication, and value-justification mechanisms in order to encourage more sustainable consumer responses.
Keywords: Environmental Sustainability in Business; Organic Food and Agriculture; Wine Industry and Tourism